Literasi Digital Melalui Realitas Virtual dalam Pembelajaran Kosakata - Aprilla Adawiyah; Irma Halimatun Sadiyah; Dinar Nursyifa; Ayu Sri Widanings (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
This article aims to describe the results of the implementation of services regarding digital literacy through virtual reality in teaching vocabulary at SDN Sindanglaka Cipanas. Virtual reality or virtual reality is a tool that can be used to assist learning. Through this virtual reality, students and teachers are invited to view 360-degree videos that are adapted to learning materials. Learning becomes more real because students can seem to see it directly. The data presented are in the form of students' pre-test and post-test results and the learning process carried out by teachers and students using virtual reality. The vocabulary taught is English vocabulary with materials in the living room and things in the bedroom. In the initial activity, the teacher was motivated first, but the teacher did not motivate students to learn using virtual reality or VR, so students were less motivated to try new things in class. The results of the students' pretest and posttest showed an increase, before learning about vocabulary using virtual reality was carried out.